Receiving newly arrived pupils: the role of evaluations in mother tongue - Sanchez-Mazas, Margarita; Changkakoti, Nilima (Revista Hipótese, 2016)
The “migrant crisis” has received a large media coverage addressing the ways to limit refugees' settlement in European countries. Although an increasing number of asylum seekers are or will be admitted in the different states, little attention is devoted to the receiving conditions in the countries of settlement. In this article, we first address some institutional, cultural and psychosocial impediments that prevent schools to fully meet the educational needs of these children. In particular, we will illustrate the often implicit processes of marginalization these pupils undergo in the classroom.
Keywords: Education; Teaching; Migrant